2019
DOI: 10.20901/ms.10.19.5
|View full text |Cite
|
Sign up to set email alerts
|

Digital Media Literacy, School and Contemporary Parenting

Abstract: Today’s societies live in a world where the media construct reality, which also affects each individual media user. Children and their parents spend most of their time with digital media and contents. Therefore, researchers emphasize the importance of digital literacy of media users. They analyse new phenomena, challenges and risks associated with the anthropological, cognitive and social development of children and young people. An important role in media and digital education is played not only by teachers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
0
10
0
3
Order By: Relevance
“…In addition, a recent study has shown that media is used with children mostly for entertainment (Labaš and Marinčić, 2016). Furthermore, digital literacy requires both education and reinterpretation with students and parents alike (Ciboci and Labaš, 2019). Finally, this study fills the gap in Croatian social studies where visual literacy is missing.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, a recent study has shown that media is used with children mostly for entertainment (Labaš and Marinčić, 2016). Furthermore, digital literacy requires both education and reinterpretation with students and parents alike (Ciboci and Labaš, 2019). Finally, this study fills the gap in Croatian social studies where visual literacy is missing.…”
Section: Introductionmentioning
confidence: 74%
“…The other study discusses visiting social network sites, sharing photos, videos etc. in the realm of digital media literacy regarding the child -parent relationship from the earliest age (Ciboci and Labaš, 2019). According to the results, only every fifth parent thinks that media education should start as early as in kindergarten (2019: 96-97).…”
Section: Conclusion: Going Beyond Datamentioning
confidence: 95%
“…It would be beneficial to investigate the participation of parents in education at school, especially in areas where there is a lack of knowledge. More extensive research is needed on how parents educate their children about media (Ciboci & Labaš, 2019).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…It is a critical parenting skill for parents to take precautions against the elements in these content that may harm their children's development. Parents' learning how to educate their children in the new digital media environment will support the healthy development of the child (Ciboci & Labaš, 2019).…”
Section: Parents and Digital Mediamentioning
confidence: 99%
“…Programi medijskog opismenjavanja u sustavu formalnog obrazovanja uglavnom se provode u sklopu medijske kulture u kurikulumu hrvatskog jezika, a neki se aspekti digitalnog opismenjavanja obrađuju na nastavi informatike. Međutim, stručnjaci (Ciboci, 2018;Ciboci i Labaš, 2019) ocjenjuju da su formalni programi medijskog opismenjavanja nedostatni i zastarjeli, da ne potiču kritičko mišljenje, da se ne bave dovoljno digitalnim medijima te da nastavnici nemaju potrebne kompetencije za podučavanje (Ciboci i Osmančević, 2015). Unatoč tomu, pozitivni pomaci ipak su vidljivi.…”
Section: Medijske Kompetencije Publikaunclassified